Public policy: a new introduction - Knill, Christoph; Tosun, Jale (Palgrave Macmillan, 2012)
A major new introduction to the theories and methods of public policy analysis and the changing nature of the policy process. Comprehensive, up-to-date and truly international in scope, it provides accessible yet sophisticated coverage of the field taking full account of global and multilevel dimensions